Long-term microbial community succession and mechanisms of regulation of dissolved organic matter derivation in livestock manure fermentation system. (July 2023) - Liu, Le; Li, Cheng; Li, Haixiao
Abstract: Industrial-scale aerobic fermentation was conducted with livestock manures. Microbial inoculation promoted the growth of Bacillaceae and consolidated its position as the dominant microorganism. Microbial inoculation substantially influenced dissolved organic matter (DOM) derivation and variations of related components in the fermentation system. The relative abundance of humic acid-like substances of DOM increased from 52.19% to 78.27% in microbial inoculation system, resulting in a high humification level. Moreover, lignocellulose degradation and microbial utilization were the important factors influencing DOM content in fermentation systems. The fermentation system was regulated by microbial inoculation, thus achieving a high level of fermentation maturity. Graphical abstract: Image 1 Highlights: High fermentation maturity was achieved by microbial regulation. Cellulose decomposition was the main reaction in fermentation systems. Bacillaceae was the dominant microorganism in microbial inoculation system. Microbial community with a high proportion of Bacillaceae promoted DOM humification.